2010
DOI: 10.1111/j.1475-3588.2010.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Suicidal Phenomena in Children Different to Suicidal Phenomena in Adolescents? A Six‐Year Review

Abstract: Background:  There has been little published about the nature and frequency of suicidal phenomena in children compared to that of adolescents. Method:  Standardised information on all presentations with suicidal phenomena to the Children’s University Hospital, Dublin from 2002 to 2008 were retrospectively analysed from a centralised database. Results:  During the time period of the study, 401 young people presented for assessment, of whom 21.9% (N = 88) were under 12 years of age. Children differed from adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
(54 reference statements)
2
24
0
Order By: Relevance
“…But, surprisingly, there was no difference in suicidality between the genders, whereas among the ten suicide attempters of the sample, the majority were girls. Sarkar et al [29] observed in a study about suicidal phenomena in children versus adolescent that, with regard to gender, the under 12s group had a higher percentage of males (57.3%) compared to females (42.7%). Moreover, in sample of adolescents, a female to male ratio of 2:1 is generally observed [30,31].…”
Section: Discussionmentioning
confidence: 98%
“…But, surprisingly, there was no difference in suicidality between the genders, whereas among the ten suicide attempters of the sample, the majority were girls. Sarkar et al [29] observed in a study about suicidal phenomena in children versus adolescent that, with regard to gender, the under 12s group had a higher percentage of males (57.3%) compared to females (42.7%). Moreover, in sample of adolescents, a female to male ratio of 2:1 is generally observed [30,31].…”
Section: Discussionmentioning
confidence: 98%
“…A comprehensive meta-analysis of the existing literature demonstrated that current psychopathology (specifically depression), prior history of suicidal ideation (SI) and/or attempt (SA), psychiatric hospitalization, and stressful or traumatic life events were consistently identified as predisposing factors [ 4 ]. Although evidence suggests that STBs begin to emerge much earlier in development [ 5 ], it remains unclear to what extent risk factors identified in adolescents and adults generalize to preadolescent children [ 6 ]. For example, some foundational studies examining younger populations (7–12 years) identified psychopathology as a risk factor for STBs [ 7 ], but this is complicated by the fact that diagnostic indicators of risk are often not yet fully evident in childhood [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Children and adolescents differ with respect to their physical, sexual, cognitive and social development, 22 and children present significant challenges in assessment for emergency department or other non-specialist staff, particularly relating to presentations of self-harm or suicide. 6,7,23,24 The reason for the rapid increase in demand during the study period requires review. In Ireland there are no studies monitoring the rates of child and adolescent psychiatric morbidly during the study period.…”
Section: Demand and Outcomementioning
confidence: 99%